2017
DOI: 10.18404/ijemst.296538
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Behavioral Engagement in Flipped and Non-Flipped Mathematics Classrooms: Teacher Abilities and Other Potential Factors

Abstract: There is a growing evidence that flipped classrooms are associated with increased levels of student engagement, as compared to engagement in "traditional" settings. Much of this research, however, occurs in post-secondary classrooms and is based upon self-reported engagement data. This study seeks to extend existing flipped classroom research by assessing behavioral engagement in flipped and non-flipped settings using observational instruments in three precollege settings. Contrary to widely-reported results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 17 publications
1
30
1
10
Order By: Relevance
“…El aula invertida ha sido implementada en diversos cursos sobre la informática (Guy y Marquis, 2016;Tanner y Scott, 2015), el inglés (Yang, 2017) y las matemáticas (Hodgson et al, 2017) con el propósito de ofrecer otras alternativas para planear, organizar y realizar el proceso de enseñanza-aprendizaje. En el curso Sistemas de información, el estudiantado de la Universidad Tennessee State consultó diversas lecturas digitales y podcasts antes de asistir a la sesión presencial y realizaron foros de discusión, evaluaciones en línea y ejercicios de forma colaborativa en el salón de clases (Guy y Marquis, 2016).…”
Section: Aula Invertidaunclassified
See 1 more Smart Citation
“…El aula invertida ha sido implementada en diversos cursos sobre la informática (Guy y Marquis, 2016;Tanner y Scott, 2015), el inglés (Yang, 2017) y las matemáticas (Hodgson et al, 2017) con el propósito de ofrecer otras alternativas para planear, organizar y realizar el proceso de enseñanza-aprendizaje. En el curso Sistemas de información, el estudiantado de la Universidad Tennessee State consultó diversas lecturas digitales y podcasts antes de asistir a la sesión presencial y realizaron foros de discusión, evaluaciones en línea y ejercicios de forma colaborativa en el salón de clases (Guy y Marquis, 2016).…”
Section: Aula Invertidaunclassified
“…En los cursos de inglés, el aula invertida permite la construcción de espacios virtuales educativos que promueven la creatividad y el rol activo del estudiantado (Yang, 2017). De hecho, este modelo pedagógico mejoró también las condiciones de enseñanza-aprendizaje sobre las matemáticas recurriendo al uso de videos antes de las sesiones presenciales y el trabajo colaborativo durante la resolución de los ejercicios en el salón de clases (Hodgson et al, 2017).…”
Section: Aula Invertidaunclassified
“…Likewise, DeSantis et al (2015) found no significant difference in student understanding when comparing pre-and posttest scores between students in flipped and traditional settings. In addition, while examining student engagement in a flipped setting, Hodgson et al (2017) examined three high school algebra classes taught under the lecture model for one unit and under the flipped model for a subsequent unit. They placed multiple observers in the classrooms to look for predetermined on-task behaviors and found that only one of the three flipped classes showed a noticeable improvement in student engagement whereas the other two did not (Hodgson et al, 2017).…”
Section: Student Performance and Engagementmentioning
confidence: 99%
“…Several studies find the flipped model improves student performance (Balaban et al, 2016;Nielsen et al, 2018;Van Sickle, 2016;Wilson, 2013) and perceptions (Buch & Warren, 2017;Wilson, 2013). Yet others find that flipping the classroom has no effect on student performance or engagement (Clark, 2015;Hodgson et al, 2017), and it results in less favorable perceptions (Jaster, 2017;Van Sickle, 2016). However, there is a dearth of research on the impact of the flipped model in an American high school math setting.…”
Section: Defining the Problemmentioning
confidence: 99%
See 1 more Smart Citation